Enhanced Thermoelectric Performance in Cu-Intercalated BiTeI by Compensation Weakening Induced Mobility Improvement - Wu, Lihua (Sci Rep, 2015)
The low weighted carrier mobility has long been considered to be the key challenge for improvement of thermoelectric (TE) performance in BiTeI. The Rashba-effect-induced two-dimensional density of states in this bulk semiconductor is beneficial for thermopower enhancement, which makes it a prospective compound for TE applications. In this report, we show that intercalation of minor Cu-dopants can substantially alter the equilibria of defect reactions, selectively mediate the donor-acceptor compensation, and tune the defect concentration in the carrier conductive network. Consequently, the potential fluctuations responsible for electron scattering are reduced and the carrier mobility in BiTeI can be enhanced by a factor of two to three between 10 K and 300 K. The carrier concentration can also be optimized by tuning the Te/I composition ratio, leading to higher thermopower in this Rashba system. Cu-intercalation in BiTeI gives rise to higher power factor, slightly lower lattice thermal conductivity, and consequently improved figure of merit. Compared with pristine BiTe(0.98)I(1.02), the TE performance in Cu(0.05)BiTeI reveals a 150% and 20% enhancement at 300 and 520 K, respectively. These results demonstrate that defect equilibria mediated by selective doping in complex TE and energy materials could be an effective approach to carrier mobility and performance optimization.